Determinants of E-participation in Government Initiatives based on Theory of Planned Behaviour: Insights from Guyana - Sarran, Dave (Journal of Information System and Informatics, 2024)
E-participation is growing increasingly relevant as a tool that facilitates citizens’ participation in policymaking and decision-making activities while studies surrounding the intention of citizens to engage with e-participation in developing countries remain limited. Thus, it is essential to understand the factors that may or may not influence a citizen’s intention to engage with e-participation initiatives in order to build successful initiatives. This study proposes a conceptual model that extends Theory of Planned Behaviour to incorporate the construct, Trust in Technology. Using data collected from an online survey of 344 Guyanese citizens, the model was tested and validated using Partial Least Square - Structural Equational Modelling (PLS-SEM). The quantitative results proved that citizens with stronger perceived behavioural control and subjective norms positively affects the intention to engage with e-participation. Additionally, the study found that attitude and trust in technology have no significant effect on citizen intention. The findings presented in this document present a vivid idea of the factors that impact citizens' intentions to participate in e-participation programmes in Guyana. These findings can help practitioners in designing effective and efficient e-participation programs.